Castoriadis : psyche, society, autonomy - Klooger, Jeff (Social and critical theory ;, 2009)
This book is an introduction to the key ideas contained in Cornelius Castoriadisa (TM) radical new theory of society and history, as well as a critical exploration of the philosophical underpinnings and implications of his reflections on Being, society and the self.